Solar Drying of Kendu (Bidi) Leaves - Paandey, C. N.; Singh, Harpal; Rath, T.; Chandra, Akash (Indian Forester, 1986)
Various types of leaves have been tried as wrapper for making bidis in different states of the country; however, the leaves of kendu (Diospyros melanoxylon) have been found to be most acceptable by the consumers, since they emit the least offensive odour on burning. The young leaves of pre-rain crop (i. e. leaves collected from first week of April upto the onset of monsoon) are generally plucked for open sun drying. The method of open sun drying involves manual labour for arranging the bundles of leaves on ground and turning them over every day for about 8 to 10 days. It bas been observed that a huge quantity of leaves, involving Crores of rupees, is destroyed annually due to discolouration of top and bottom leaves in each bundle and being blown off by wind. An attempt has therefore, been made to reduce this huge loss, by drying the kendu leaves under controlled condition, In a solar air-heated chamber. A solar air-heated chamber with a capacity of drying about 35,000 leaves in one charge was designed, fabricated and tested for a pilot scale trial at Angul, by the Forest Department, Orissa. It has been Found that the process can be easily adopted for drying the kendu leaves on large scale. The details of the process are described.